The Relationship Between Immunization Status and Infectious Diseases in Children: A Literature Review - Feby Artha Ayu Mefian; Atha Faiza Anindya Putri Sunoto; Siti Rahmatul Maulidiyah; Manzilah El Inayah; Satriya Pranata (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Infectious diseases remain the leading cause of morbidity and mortality among children. WHO data from 2023 indicate that approximately 14.5 million children worldwide are not immunized, including a significant number in Indonesia. Objective: This study aims to analyze the relationship between immunization status and the incidence of infections in children through a literature review. Methods: This study employed a systematic literature review approach. The literature search focused on publications from the past 10 years that were available in full text. Most of the analyzed studies used an analytical observational design. Data were collected from primary studies. Data analysis in the reviewed studies generally employed statistical tests such as the chi-square test, logistic regression, and multivariate analysis to determine the relationship between immunization status and the incidence of infections. Several large-scale studies also used logistic regression and multilevel models to control for confounding factors such as nutritional status, parental education, and access to health care. Results: The findings indicate that the majority of studies report an association between immunization status and the incidence of infectious diseases. Children with incomplete immunizations have a higher risk of developing infections such as acute respiratory infections (ARIs) and pneumonia. Variations in results are influenced by other factors such as nutritional status, environment, and access to health care. The conclusions indicate that immunization status plays a crucial role in reducing the incidence of infectious diseases in children, although this association is influenced by various other factors. Conclusion: The results of this analysis underscore the importance of increasing immunization coverage and adopting a comprehensive approach to the prevention of infectious diseases in children